Photography in Los fantasmas del masajista by Mario Bellatin (2019)
This paper reflects on the visual stimuli present in the work of the Peruvian/Mexican writer Mario Bellatin, specifically in the direct incorporation of photographs in Los fantasmas del masajista (2009). In this way, four conceptual axes are proposed that seek to illustrate the meaning of the inclusion of this element in the text, as well as the analysis of the photographic archive that, at first sight, seem to have an obvious continuity with the story, but that many times rather puzzle and produce a derisory effect. Finally, interdisciplinarity is considered as a procedure that, far from favoring referentiality in the work, arouses a series of doubts in the reader, an effect that is directly related to the artistic proposal of this writer.